OP41 The health of people experiencing multiple forms of social exclusion: a systematic review. (3rd September 2019) - Tweed, EJ; Sumpter, C; Thomson, R; Lewer, D; Southworth, P; Kirolos, A; Story, A; Hayward, A; Hwang, S; Aldridge, R; Katikireddi, SV
Abstract : Background: People with a history of homelessness, imprisonment, substance use, sex work, or serious mental illness experience much higher rates of ill-health and premature death than the general population. There is substantial overlap in these experiences in the population, and they may interact in important ways to influence health. However, the health outcomes associated with these experiences in combination have not previously been reviewed. We therefore aimed to synthesise existing evidence on all-cause mortality; cause-specific mortality; morbidity from conditions appearing in ICD-10; self-rated health; and quality of life among people with lifetime exposure to more than one of the following: homelessness; imprisonment; substance use; sex work; or serious mental illness. Methods: We searched Medline, Embase, and Psycinfo using search terms for the above exposures and outcomes, in consultation with a medical librarian. Eligible studies comprised peer-reviewed English-language articles from high-income countries published since 1998 reporting at least one relevant outcome for people with lifetime exposure to two or more exposures of interest, in comparison to people with one or no exposures. Screening was undertaken independently by two authors using Covidence, with risk of bias assessed using a modified Newcastle-Ottawa Scale. Findings were summarised using a pre-specified narrative synthesis plan. The protocol was registered with PROSPERO (CRD42018097189). Results: Searches retrieved 15, 948 unique citations. After full text screening of 1, 583 studies, initial results from 293 studies for which data extraction has been completed are presented here. Of these, 73% were cross-sectional studies. The most common exposure combinations were imprisonment & substance use (33%) and serious mental illness & substance use (26%); only 11 data points (1%) reported outcomes associated with >2 exposures. Infectious diseases were by far the most common outcomes studied (44%): blood-borne viruses alone accounted for 33% of all data points. The next most common outcomes were external causes, injury, and poisoning (16%) and mental disorders (14%): together with infections, these categories accounted for 73% of all data points. Conclusion: Existing research on the health of people experiencing multiple forms of social exclusion is dominated by cross-sectional studies examining a relatively limited set of exposures and outcomes. The lack of data on more than two exposures in combination; self-rated health or quality of life; or non-communicable diseases (e.g. cardiovascular disease and cancer) suggests that research to date may not reflect the true burden of ill-health in these populations. Limitations include restriction to peer-reviewed studies and risk of publication bias.